The Effect of the Implementation of the School Field Introduction Program (PLP) on the Motivation to Become a Professional Teacher in Economic Education Students of FKIP Sriwijaya University for the 2019 Academic Year - Nadari*, Nadari; Jaenudin, Riswan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to demonstrate the impact of the School Field Introduction (PLP) program on students of economics education at FKIP Sriwijaya University's motivation to become professional teachers for the 2019 academic year. The examples in this study were all Financial aspects Schooling understudies at FKIP Sriwijaya College for the 2019 scholarly year, adding up to 65 individuals. Questionnaires, interviews, and documentation were the methods used to collect data. Instrument legitimacy was done utilizing the Item Second Connection recipe and dependability testing utilizing Cronbach's Alpha. The information examination procedure in this study utilized the consequences of a poll made by the scientist. The consequences of the review showed that there was an impact of the execution of the School Field Presentation (PLP) program on the inspiration to turn into an expert educator in Financial matters Training understudies at FKIP Sriwijaya College. The magnitude of the partial hypothesis testing (t-test) calculation results obtained by tcount 10.986 ttable 1.669 demonstrates this: when the School Field Introduction (PLP) program is implemented, Ho is rejected and Ha is accepted. The consequences of the computation of the determinant coefficient (r2) got a consequence of 0.6570, demonstrating that the inspiration to turn into an expert educator in Financial matters Training understudies at the Sriwijaya College FKIP in the 2019 scholastic year was impacted by 65.7% by the execution of the School Field Presentation (PLP) program, while the excess was 34 .3% is affected by different factors that are not analyzed in this review.